Authority in prayer : praying with power and purpose - Sheets, Dutch (Minneapolis, Minn. : Bethany House, 2006)
"Dutch Sheets shows how believers don't need to walk in weakness and powerlessnes but can take hold of God's promises and be the overcomers He intends them to be. For Christians who desire to pray with greater effectiveness and strength"--Provided by publisher.
The question -- The author -- The poet -- The assignment -- The contest -- The ekklesia -- The dynasty -- The voice -- The sword -- The heavens -- The room -- The interruption -- The levels -- The degrees -- The gains.
Includes bibliographical references.
Keywords: Prayer -- Christianity